2018
DOI: 10.4236/jbcpr.2018.64016
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Change Orders in the Jordanian Construction Industry

Abstract: Change orders are common and clearly noticeable in Jordanian construction industry. Several studies have identified change orders as significant problem in Jordanian construction projects, and they mainly cause delay and cost overrun. This situation spurs the researchers for investigating the significant causes of change orders in construction projects. Thus, this paper aims to determine the main causes of change orders in the Jordanian construction private sector which responsible for significant cost overrun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 20 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…Similarly, Lature and Hinge [22], through an extensive questionnaire and two case studies, identified 16 causes of design change, and concluded that of the variables that induce changes in construction projects, changes in scope or plan by the owner are the most common. In the private Jordanian construction sector, design change causes that are responsible for cost overrun are broken down into three main categories: engineering causes, causes related to clients, and circumstances of the project, with four, four, and two causes, respectively [8]. Additionally, a correlation was established to understand the relationship between the causes of change for each category.…”
Section: Causes Of Design Changementioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Lature and Hinge [22], through an extensive questionnaire and two case studies, identified 16 causes of design change, and concluded that of the variables that induce changes in construction projects, changes in scope or plan by the owner are the most common. In the private Jordanian construction sector, design change causes that are responsible for cost overrun are broken down into three main categories: engineering causes, causes related to clients, and circumstances of the project, with four, four, and two causes, respectively [8]. Additionally, a correlation was established to understand the relationship between the causes of change for each category.…”
Section: Causes Of Design Changementioning
confidence: 99%
“…The internal validity of quantitative techniques is attained by structuring a questionnaire to quantify what it is intended to quantify [8], a technique which was employed in this study. For all three subdivisions, the external validity was determined by using a sufficient number of participants who represented various industry players.…”
Section: Conflict Between Contract Documentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Change or variation orders are two terms that are usually used interchangeably in practice (Jarkas and Mubarak, 2016). Some definitions specify change orders as variation orders (Alshdiefat and Aziz, 2018). One of the significant situations facing the construction project is a matter of variation orders during the construction phase (Mohammad, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%